Exploratory Factor Analysis and Reliability of the Child Welfare Trauma-Informed Individual Assessment Tool. Issue 1 (1st January 2017) - Madden, Elissa E.; Scannapieco, Maria; Killian, Michael O.; Adorno, Gail
Abstract : This article presents the development and psychometric analysis of the Child Welfare Trauma-Informed Individual Assessment Tool, an instrument designed to measure the extent to which child welfare service providers employ trauma-informed practices with the children and families that they serve. Using the responses of 213 front-line child welfare workers, exploratory factor analysis was used on a seventeen-item scale, resulting in a four-factor model. Based on the results of this analysis, implications for potential uses of the instrument are discussed, and specifications for additional evaluation of the measure's validity are outlined.